A novel pyrene based highly selective reversible fluorescent-colorimetric sensor for the rapid detection of Cu2+ ions: application in bio-imaging. Issue 9 (15th February 2018) - Ghorai, Anupam; Mondal, Jahangir; Manna, Amit Kumar; Chowdhury, Shubhamoy; Patra, Goutam K.
Abstract : A simple, low-cost pyrene derivative containing a benzilmonohydrazone moiety has been exploited for the selective detection of Cu 2+ by colorimetric, absorption, emission and bio-imaging methods. The sensitivity of the fluorescence based assay is 7.8 nM for Cu 2+, which is far below the limit mentioned in the World Health Organization. Abstract : A novel pyrene derivative containing a benzilmonohydrazone moiety has been prepared following a facile synthetic procedure and exploited for the selective detection of Cu 2+ under four different channels (colorimetric, absorption, emission and bio-imaging). In the presence of Cu 2+, the chemosensorL provided a significant fluorescence enhancement with an easily detectable colour change from yellow to colourless, whereas other metal ions produced only minor changes in colour or fluorescence intensity. The sensitivity of the fluorescence based assay is 7.8 nM for Cu 2+, which is far below the limit mentioned in the World Health Organization (WHO) guidelines for drinking water. 1 H NMR data, the Job plot and the ESI-MS spectrum prove 1 : 1 stoichiometric complexation betweenL and Cu 2+ . The sensing behaviour of the probe has also been well supported by DFT studies. ReceptorL exhibits remarkable detection ability in a wide pH range of 4–11 and is successfully utilised in the determination of Cu 2+ in real samples. Moreover, L shows its application potential in the detection of Cu 2+ in living cells.